Plan de negocios para la creación y comercialización de una revista empresarial, cantón Quevedo, año 2014 - Guerrero López, Jessenia Mariuxi (2015)
The research was conducted with the purpose of the un develop the business plan for the creation and marketing of a business magazine, Quevedo City, 2014, I addressed to meet the needs of customers with a product and content quality, aimed at economically active, with the purpose of personalities using the average content of this for business to embark on their own business. With market study Through Polls If you could know the preferences, needs, likes, those customers when buying a magazine, and the costs paid by this product and service, determining budgets and checking of the idea of creating feasible business. The initial investment for start-up business is $ 42.753.00 US dollars, the same as it has a value of $ 22,753.00 in cash and the balance will be financed by a bank loan of $ 20,000.00. According to the obtained results it was found that the equilibrium point in the research process, determined that economic indicators reflect the version we can deduce net real value of the (NPV) of $21.237.97, and the rate internal return (IRR) of 36% for project implementation…. .